Social Trust and Fake News: Study Among College Students in West Java, Indonesia - Dulkiah, Moh. (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2023)
This study examines students' views on the phenomenon of fake news as fake news through social media. This study aims to find out how students' attitudes respond to fake news in universities in West Java, Indonesia. Data collection was carried out using in-depth interviews and documentation studies to explore the research focus. This study found several things, namely: most students believed in the news that was spread and accepted fake news. Even some students have been the creators and spreaders of fake news. Second, the spread of fake news is done through social media along with the development of information technology. Third, there are 4 (four) patterns of spreading fake news among university students, namely (1) cyclization patterns (formation of circular patterns in organic compounds or B related to cycles) (2) limited distribution patterns; pattern of free spread, and (4) pattern of breaking up (dissemination of information stops at the authorities). This study concludes that students' social trust in fake news is related to awareness of media literacy among them.